A Flow-Partitioned Unequal Clustering Routing Algorithm for Wireless Sensor Networks - Jian Peng; Xiaohai Chen; Tang Liu (International Journal of Distributed Sensor Networks)
Energy efficiency and energy balance are two important issues for wireless sensor networks. In previous clustering routing algorithms, multihop transmission, sleep scheduling, and unequal clustering are always used to improve energy efficiency and energy balance. In these algorithms, only the cluster heads share the burden of data forwarding in each round. In this paper, we propose a flow-partitioned unequal clustering routing (FPUC) algorithm to achieve better energy efficiency and energy balance. FPUC consists of two phases: clustering and routing. In the clustering phase, the competition radius is computed according to the node density and the distance from sensor nodes to the sink. The sensor nodes that have more residual energy and larger overlapping degree have higher probability to be selected as cluster heads. In the routing phase, each cluster head first finds the gateway nodes and then distributes the data flow to each of its gateway nodes depending on residual energy. After that, each gateway node forwards the data to the next hop with minimum cost. Two metrics called network lifetime and coverage lifetime are used to compare the performance of FPUC with that of the existing ones. Simulation results show that FPUC can achieve longer network lifetime and coverage lifetime than previous algorithms.